2015
DOI: 10.5194/acp-15-12705-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of continuous anthropogenic CO<sub>2</sub>: model-based evaluation of CO<sub>2</sub>, CO, δ<sup>13</sup>C(CO<sub>2</sub>) and Δ<sup>14</sup>C(CO<sub>2</sub>) tracer methods

Abstract: Abstract. We investigate different methods for estimating anthropogenic CO 2 using modeled continuous atmospheric concentrations of CO 2 alone, as well as CO 2 in combination with the surrogate tracers CO, δ 13 C(CO 2 ) and 14 C(CO 2 ). These methods are applied at three hypothetical stations representing rural, urban and polluted conditions. We find that, independent of the tracer used, an observation-based estimate of continuous anthropogenic CO 2 is not yet feasible at rural measurement sites due to the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
1
38
1
Order By: Relevance
“…Given both increasing and increasingly uncertain anthropogenic emissions (Ballantyne et al, 2015), this method might also provide an approach complementing the 14 CO 2 -based method of investigating CO 2, A (Gamnitzer et al, 2006;Vardag et al, 2015). As also pointed out in our study, the approach has some caveats such as the uncertainty associated with the secondary production of CO from VOC oxidation, which should be investigated in more detail.…”
Section: Discussionmentioning
confidence: 77%
“…Given both increasing and increasingly uncertain anthropogenic emissions (Ballantyne et al, 2015), this method might also provide an approach complementing the 14 CO 2 -based method of investigating CO 2, A (Gamnitzer et al, 2006;Vardag et al, 2015). As also pointed out in our study, the approach has some caveats such as the uncertainty associated with the secondary production of CO from VOC oxidation, which should be investigated in more detail.…”
Section: Discussionmentioning
confidence: 77%
“…However, the disadvantage of using such a bottom-up approach is that usually only information from a few specific sites are available, which need then to be upscaled correctly such that they are representative of the entire catchment area. For a determination of δ F during the entire year, one can possibly utilize 14 C(CO 2 ) and CO/CO 2 measurements (following Vardag et al (2015b)) or O 2 /N 2 measurements (e.g., Sturm et al 2006;Steinbach et al, 2011), all of which exhibit their own deficiencies, which are discussed elsewhere (e.g., Ciais et al, 2015;Vardag et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…An uncertainty of ±2.5 ‰ for δ F is rather large if we want to use this observation-based top-down result for further quantitative source apportionment. Vardag et al (2015b) showed that a misassignment of 2.5 ‰ in δ F leads to a bias in the continuous fuel CO 2 estimate of about 15 % for an urban measurement site like Heidelberg. The observation-based biospheric end member δ bio has an uncertainty of only about 1.0 ‰ in Figure 5.…”
Section: Evaluation Of δ S In Heidelbergmentioning
confidence: 99%
See 1 more Smart Citation
“…The fossil fuel offsets were removed using the CO:CO 2 ratios from road traffic sources after removing a baseline from the observations. The use of CO as a combustion tracer and for inverse model studies was successfully demonstrated in previous studies (e.g., Gerbig et al 2003;Vardag et al 2015). In contrast to the four other observation towers that are located in rural and remote regions, regional and local anthropogenic emissions of CO 2 significantly affect the measured mixing ratios at the OSI tower that represents the large Willamette valley ecoregion.…”
Section: Assessment Of Observational Errorsmentioning
confidence: 97%